Relations Among Chronic Peer Group Rejection, Maladaptive Behavioral Dispositions, and Early Adolescents' Peer Perceptions. Issue 3 (7th January 2014) - Ladd, Gary W.; Ettekal, Idean; Kochenderfer‐Ladd, Becky; Rudolph, Karen D.; Andrews, Rebecca K.
Abstract : Adolescents' perceptions of peers' relational characteristics (e.g., support, trustworthiness) were examined for subtypes of youth who evidenced chronic maladaptive behavior, chronic peer group rejection, or combinations of these risk factors. Growth mixture modeling was used to identify subgroups of participants within a normative sample of youth ( N  =   477; 50% female) for whom data had been gathered from fifth grade ( M age  = 10.61) through eighth grade ( M age  = 13.93). Results revealed that both enduring individual vulnerability (i.e., chronic withdrawn or chronic aggressive behavioral dispositions) and interpersonal adversity (i.e., chronic peer group rejection) were linked with either differences or changes in adolescents' perceptions of their peers' supportiveness and trustworthiness across the early adolescent age period.